DESCRIPTION CRITERIA FORMING OF HIGH SCHOOL STUDENTS’S ART-GRAPHICS CULRURE (Journal of Information Technologies in Education (ITE), 2014)
The article deals the possibilities of for formation of the art-graphics culture of high school students. Сriteria, indicators and levels of its evaluation are identified in the article.
Keywords: art-graphics culture; criteria; indicators and levels of its formation